Development and Characterization of Pineapple Fibre Nonwovens for Thermal and Sound Insulation Applications. Issue 10 (2nd October 2020) - Thilagavathi, G.; Muthukumar, N.; Neela Krishnanan, S.; Senthilram, T.
ABSTRACT: Due to the environmental damage caused by synthetic materials, natural fibers are gaining importance day by day. Apart from the conventional sources of fibers, researchers are interested in some underexploited fibers, which are having high potential applications in textiles. Pineapple leaf fiber (PALF) is an agro residue, extracted by scratching of pineapple leaves. In this study, pineapple fibers were extracted from pineapple leaves by raspador technique. The physical, morphological, and thermal properties of pineapple fibers were characterized. The nonwovens were developed from 100% pineapple fibers and also by blending low melting point polyester with pineapple fibers by needle punching technique. The developed nonwovens were characterized for sound and thermal insulation applications. It was found that nonwovens made by blending PALF with low melt PET had better thermal and sound insulation characteristics compared to the nonwovens made from 100% PALF fibers.